Penerapan Keadilan Restoratif pada Tahap Penyelidikan Pasca Undang-Undang No.20 Tahun 2025 Ditinjau dari Perspektif Asas Praduga Tidak Bersalah - Wildan Ashar; Ummi Maskanah (Jurnal Hukum Lex Generalis, 2026)
The implementation of restorative justice at the investigation stage reflects a development in the Indonesian criminal justice system that emphasizes recovery rather than mere punishment. This study examines the mechanism for implementing restorative justice during the investigation stage and its relation to the presumption of innocence principle. The study aims to analyze the legal basis and implementation of restorative justice in the investigation process. The research method used is normative legal research employing statutory and conceptual approaches. Data were obtained through library research consisting of primary, secondary and tertiary legal materials analyzed qualitatively. The results indicate that the implementation of restorative justice at the investigation stage has obtained a legal basis through Police Regulation Number 8 of 2021 as well as the provisions of Article 79 and Article 83 of criminal procedural law. The mechanism is carried out through an agreement between the victim and the offender facilitated by investigators. Its implementation must still uphold the presumption of innocence, protection of the parties’ rights, and proper supervision to ensure legal certainty and substantive justice.